N‐Doping Coupled with Co‐Vacancies Activating Sulfur Atoms and Narrowing Bandgap for CoS Toward Synergistically Accelerating Hydrogen Evolution - Zeng, Ping; Meng, Yang; Liu, Zhan; Sun, Guo‐Qi; Li, Xiao‐Yun; Yang, Xiao‐Yu; Ye, Cui‐Fang; Li, Yu; Liu, Jin‐Ping; Chen, Li‐Hua; Su, Bao‐Lian; Wang, Yi‐Long (Small (Weinheim an der Bergstrasse, Germany), 2023)
The combination of hetero‐elemental doping and vacancy engineering will be developed as one of the most efficient strategies to design excellent electrocatalysts for hydrogen evolution reaction (HER). Herein, a novel strategy for N‐doping coupled with Co‐vacancies is demonstrated to precisely activate inert S atoms adjacent to Co‐vacancies and significantly improve charge transfer for CoS toward accelerating HER. In this strategy, N‐doping favors the presence of Co‐vacancies, due to greatly decreasing their formation energy. The as‐developed strategy realizes the upshift of S 3p orbitals followed by more overlapping between S 3py and H 1s orbitals, which results in the favorable hydrogen atom adsorption free energy change (ΔGH) to activate inert S atoms as newborn catalytical sites. Besides, this strategy synergistically decreases the bandgap of CoS, thereby achieving satisfactory electrical conductivity and low charge‐transfer resistance for the as‐obtained electrocatalysts. With an excellent HER activity of −89.0 mV at 10.0 mA cm−2 in alkaline environments, this work provides a new approach to unlocking inert sites and significantly improving charge transfer toward cobalt‐based materials for highly efficient HER. A novel strategy for N‐doping coupled with Co‐vacancies is demonstrated to precisely activate inert S atoms adjacent to Co‐vacancies and significantly improve charge transfer for CoS toward accelerating HER. The upshift of the S 3p orbitals and more overlapping between the S 3py and H 1s orbitals are the key reasons for activating such S atoms. Besides, this strategy synergistically decreases the bandgap of CoS, thereby achieving efficient charge transfer during HER.